Combining contrast-enhanced ultrasound and blood cell analysis to improve diagnostic accuracy of plasma cell mastitis. Issue 2 (January 2022) - Zheng, Yan; Wang, Lin; Han, Xiu; Shen, Lin; Ling, Chen; Qian, Zhongping; Zhu, Lin; Dong, Fenglin; Han, Qingzhen
Plasma cell mastitis is a benign suppurative disease of the breast, lack of specific clinical manifestations, which is easy to be misdiagnosed and mistreated, often confused with mastitis, breast cancer (BC), and other diseases. Thus, we aimed to establish a combined model of promoting diagnostic accuracy of plasma cell mastitis by contrast-enhanced ultrasound (CEUS) patterns and routine blood cell analysis. Eighty-eight plasma cell mastitis, 91 breast cancer, and 152 other benign breast diseases' patients grouped according to pathological diagnosis underwent CEUS and blood cell analysis examination; 100 healthy female donors were involved. All the plasma cell mastitis and breast cancer patients presented hyperenhancement of CEUS breast lesions compared with others. The majority of plasma cell mastitis (65/88) showed perfusion defect of CEUS patterns with smooth edge (56/65) and multiple lesions (49/65); in contrast, fewer breast cancer patients (30/91) displayed perfusion defect. White blood cell count (WBC), neutrophils, and neutrophils/lymphocytes ratio of blood cell analysis in plasma cell mastitis patients increased significantly compared with other patients ( P  < 0.0001). Combining perfusion defect of CEUS patterns and WBC yielded an area under the receiver operating characteristic curve of 0.831, higher than single 0.720 and 0.774, respectively. The cut-off value of WBC (7.28 × 10 9 /L) helped remaining 65.2% (15/23) atypical cases to be correctly diagnosed as plasma cell mastitis, not misdiagnosed as breast cancer. In conclusion, CEUS presented a clear perfusion defect pattern of plasma cell mastitis lesion for the first time. A precise WBC by routine blood cell analysis test can assist CEUS examination in the differential diagnosis of plasma cell mastitis and breast cancer. It is a promised combination for laboratory diagnostic of PCM.